Identification of two-dimensional layered dielectrics from first principles - Mehrdad Rostami Osanloo (Nature Portfolio, 2021)
Developments in the field of two-dimensional van der Waals materials offer big promise for device applications. This study reports a first-principle investigation on the dielectric properties of 32 exfoliable two-dimensional layered dieletrics for assessing the prospects of these materials in devices.